1983
DOI: 10.1007/bf00238781
|View full text |Cite
|
Sign up to set email alerts
|

Stance posture control in select groups of children with cerebral palsy: Deficits in sensory organization and muscular coordination

Abstract: This study has focused upon the automatic components of posture and movement in a group of ten cerebral palsy children carefully selected to represent a spectrum of abnormalities relatively pure by clinical standards and ten age-matched normals. Each subject stood unsupported upon a movable platform and within a movable visual surround and was then exposed to external perturbations or was asked to pull with one arm upon a movable handle. In comparing the performance of cerebral palsy children in each clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
199
3
4

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(215 citation statements)
references
References 27 publications
9
199
3
4
Order By: Relevance
“…Many previous studies on CPAs to external perturbations (e.g., support surface translation) have revealed that a higher degree of antagonistic coactivation of ventral and dorsal postural muscles is a primary characteristic in individuals with SDCP (Burtner et al 1998;Nashner et al 1983;. In the present study, the percentages of trials with anticipatory antagonistic coactivation in the thigh and lower leg tended to be higher in the SDCP group than in the control group.…”
Section: Discussionsupporting
confidence: 50%
“…Many previous studies on CPAs to external perturbations (e.g., support surface translation) have revealed that a higher degree of antagonistic coactivation of ventral and dorsal postural muscles is a primary characteristic in individuals with SDCP (Burtner et al 1998;Nashner et al 1983;. In the present study, the percentages of trials with anticipatory antagonistic coactivation in the thigh and lower leg tended to be higher in the SDCP group than in the control group.…”
Section: Discussionsupporting
confidence: 50%
“…Children with CP exhibit an increase in co-contractions of the proximal and distal muscles, with no coordinated proximal-distal pattern 26 . According to Nashner et al 27 , CP children present an inverse order of distal and proximal activation and muscle synergies, which compromises responses to disequilibrium. Findings described in the literature demonstrate that treadmill training provides improvements in gait velocity 17,19 , gross motor function 15,20 and the kinematic pattern of the lower limbs 20 .…”
Section: Control N=7mentioning
confidence: 99%
“…Sports activities also require proper balance control. The visual, somatosensory, and vestibular systems all contribute to the maintenance of balance (10) and may be adversely affected by musculoskeletal injury, head trauma, disease, or aging. These influences on the visual, somatosensory, and vestibular systems might decrease a person's ability to perform dynamic activities and, thus, impede normal daily functioning (2,6,17,23).…”
mentioning
confidence: 99%